(untitled) (Ameghiniana, 2013)
The geology and palaeontology of La Alumbrera river region, in Catamarca Provínce are here described. The sequence is made up by the shales of the La Alumbrera Formation (Ordovician) intruded by granites of Ñuñorco Formation (Ordovícian-Sílurian.) The Upper Paleozoíc is made up by sandstones and shales of the Agua Colorada and La Cuesta Formations which are overlaíd by the Rio Colorado Formatíon (Upper Tertiary). The Ordovician rocks contain a fauna with Tetragrapius quadribrachiatus, T. bigsbyi, T. approximatus, T. cf. T. phyllograptoides, T. amii, T. serra, T. quadribrachiatus val’. catuaensis, Didqmograptus cf. D. extensus, D. cf. D. niudus, Clonograptus rígidus, Clonograptus sp. y Caryocaris sp. The fauna point to a Lower Ordovician age (Arenigian).